2016
DOI: 10.4081/jlimnol.2016.1535
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heterogeneity at different scales: key factors affecting caddisfly larvae assemblages in standing waters within a lowland river catchment

Abstract: <p>We examined the importance of environmental parameters at different spatial scales influencing the occurrence of caddisfly larvae at different levels of their organization (species, faunistic metrics and functional groups) in lentic floodplain waters, in order to gain information on the ecological status and management of a small lowland river catchment. <br />At the lowest spatial level – pH, sediment grain size, insolation and the presence of aquatic macrophytes proved significant for caddisfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…As the findings from this work have shown (CCAs), the process of colonisation requires the presence of small water bodies in the neighbourhood that supply an important pool of species. An identical relationship was found among the caddisflies of standing waters in the valley of a small lowland river (Buczyńska et al, 2017). This is because many lacustrine littoral species also colonise small bodies of standing water (Wallace, 1991) and migrate freely among them.…”
Section: Functional Groups Of Caddisflies Of the Storage Reservoirsmentioning
confidence: 73%
See 2 more Smart Citations
“…As the findings from this work have shown (CCAs), the process of colonisation requires the presence of small water bodies in the neighbourhood that supply an important pool of species. An identical relationship was found among the caddisflies of standing waters in the valley of a small lowland river (Buczyńska et al, 2017). This is because many lacustrine littoral species also colonise small bodies of standing water (Wallace, 1991) and migrate freely among them.…”
Section: Functional Groups Of Caddisflies Of the Storage Reservoirsmentioning
confidence: 73%
“…The most important were the physical and chemical parameters of the water, followed by structural factors; the least important were factors associated with buffer zones. A number of authors (Galbraith et al, 2008;Skuja and Spungis, 2010;Savić et al, 2013;Buczyńska et al, 2017) consider the parameters of water to be of greater significance than the water body's structure and/or its surroundings/ catchment area as regard the distribution of caddisfly larvae in natural waters. Even though the percentage of explained variance in each category of factors obtained by those authors and in the present work is not always high (9-40%), it is clear that these insects À as expected from their mode of life À are affected by factors acting at different spatial levels.…”
Section: Three-level Spatial Factors Influencing the Distribution Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In opposition to this, there are the springs from the locality of Z1, where there was only a small water bodies element, resulting from the dominant influence of flood waters. Crenobiontic fauna have a much less significant dispersal ability than rheobiontic fauna and therefore the damaged fauna is reborn much more slowly even the same environmental conditions ( Szlauer-Łukaszewska & Zawal, 2014 ; Stępień et al., 2015 ; Zawal et al, 2015 ; Zawal et al, 2016a ; Zawal et al, 2016b ; Zawal et al, 2016c ; Zawal et al, 2017 ; Dąbkowski et al., 2016 ; Płaska et al., 2016 ; Buczyński et al, 2016 ; Pakulnicka et al, 2016a ; Pakulnicka et al, 2016b ; Buczyńska et al., 2017 ; Gerecke, Martin & Gledhill, 2017 ). We did not find any rhitrobiontic species in flooded springs: these were dominated by lenitobionts and to a lesser extent by crenobionts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of the Krąpiel valley showed environmental factors to be acting at different levels of organization in the environment, i.e., (1) the landscape level, (2) the macrohabitat level and (3) the mesohabitat level; they all affect the species composition and the abundance of water mite assemblages ( Stryjecki et al, 2016 ; Buczyńska et al., 2017 ; Zawal et al, 2016b ; Zawal et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%